A kind of paint-free memory nano nylon resin and preparation method thereof
Through the introduction of amino seal -end hard segments and polyphraphy sutrication in nylon materials, the modified nylon of the micro -phase separation structure is formed to solve the problem of insufficient mechanical performance of the existing nylon material and achieve better shape memory and process simplification.
Patent Information
- Application Number
- CN202410809057.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-21
AI Technical Summary
The existing shape memory nylon materials have shortcomings in mechanical properties and chemical stability, which limits their development in practical applications.
By preparing amino sealing nylon as a hard segment, and forming a soft segment with the materials such as polypholine amu, a modified nylon is formed after the hard and soft segment aggregation. performance.
The prepared modified nylon has better rigidity, flexibility and resilience, and can quickly restore its original shape after deformation. At the same time, because it does not require spray painting, the process is simpler.
Smart Images

Figure BDA0004905647510000081 
Figure BDA0004905647510000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer compound compositions, and in particular to a paint-free memory nano nylon resin and a preparation method thereof. Background Art
[0002] Materials that can respond to external factors such as temperature, magnetic field or light and return to their original shape are called shape memory materials. In particular, shape memory polymers are favored due to their easy preparation, low-cost production, excellent shape memory function and high customizability, and have been used in many fields including medicine, self-healing materials, aerospace and heat shrinkable materials. The main matrices of these polymers include polyester, polyurethane and polyethylene. At present, shape memory polymers face some challenges in practical applications, mainly due to the limitations of their matrix materials themselves, such as insufficient mechanical strength and poor chemical stability, which limit the further application and development of shape memory materials.
[0003] CN202011163136.6 discloses a nylon 6 composition with excellent shape memory performance, which is prepared by the following components in parts by weight: 100 parts of caprolactam, 5-10 parts of caprolactone, 1-2 parts of catalyst, 0.5-1 parts of activator, 3-5 parts of needle-shaped nano-hydroxyapatite, and 1-2 parts of antioxidant. The invention also discloses a method for preparing the above-mentioned nylon 6 composition. The invention can significantly increase the shape memory performance of the composition by adding caprolactone and needle-shaped nano-hydroxyapatite to caprolactam with a reasonable ratio. Excess caprolactone, excessive needle-shaped nano-hydroxyapatite, and hydroxyapatite with a larger particle size or spherical particle size cannot increase the shape memory performance of the composition.
[0004] CN201410247150.2 discloses a memory nylon rubber and plastic material, which is made of the following components in mass percentage: modified nylon, maleic anhydride graft copolymer, and additives; wherein the modified nylon is prepared from caprolactam: 35-42%; terminal vinyl phenyl silicone oil: 5-25%; initiator: 0.1-0.5%; aromatic diacid: 1-10%; polyether: 15-40%; catalyst: 0.1-1.1%; chain extender: 1-10%; antioxidant: 0.5-1.5%. The invention also discloses a preparation method of the above memory nylon rubber and plastic material. The invention uses the polyamide hard segment of terminal vinylphenyl silicone oil to modify nylon to enhance the comprehensive properties of nylon such as low-temperature toughness, oxidation resistance, weather resistance, heat resistance and flame retardancy, and uses maleic anhydride grafted copolymer to toughen and modify nylon to obtain nylon rubber-plastic materials with plastic and rubber properties, improve the shape recovery memory effect and comprehensive mechanical properties, overcome the problems of poor elasticity and shape recovery of ordinary nylon or plastic materials, and enhance the memory of products such as headphone cables.
[0005] As a high-performance engineering plastic, nylon contains a large number of polar amide bonds in its molecular structure. These bonds form strong hydrogen bonds between the molecular chains, which enhances the cohesion of the material. At the same time, the molecular chain of nylon is highly regular, resulting in a high degree of crystallinity. It is worth mentioning that the methylene groups in the nylon molecular chain bring it good flexibility. In addition to excellent mechanical properties, nylon also exhibits excellent low-temperature performance, electrical insulation properties and chemical stability. Therefore, using nylon as a matrix material to develop new shape memory materials is expected to give this type of material more excellent performance and open up a broader market prospect for it. However, there is currently little research on nylon-based shape memory materials and there are defects such as insufficient mechanical properties, which need to be solved urgently. Summary of the invention
[0006] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a paint-free memory nano-nylon resin and a preparation method thereof.
[0007] Due to the poor dimensional stability, poor low-temperature toughness, heat resistance and toughness of nylon materials, its application in the field of shape memory materials is limited. In the present invention, amino-terminated nylon is first prepared as a matrix, which, as a hard segment with a moderate molecular weight, can not only play the role of fixing the material, but also will not make the material have high strength and modulus due to the high molecular weight, and cannot perform shape memory behavior, and then (bibenzyl-4,4'-diyl) diisocyanate, polytetrahydrofuran, and trimethylolpropane are mixed to obtain a soft segment, thereby playing the role of a deformable material, and the hard and soft segments are polymerized to obtain a modified nylon, and the soft and hard segments form a microphase separation structure in the system. The construction of the microphase separation structure plays a decisive role in shape memory, so the prepared modified nylon has strong rigidity, good flexibility, and excellent resilience, so it can quickly restore its original shape after deformation. Styrene-butadiene-acrylonitrile copolymer can provide good gloss to the material, so the obtained resin has good gloss, no need for spray painting, and the process is simpler when applied.
[0008] To achieve the above purpose, the present invention provides a paint-free memory nano nylon resin, which includes the following raw materials in parts by weight: 40 to 70 parts of modified nylon, 10 to 20 parts of styrene-butadiene-acrylonitrile copolymer, 5 to 10 parts of compatibilizer, 0.5 to 5 parts of antioxidant, 2 to 10 parts of lubricant, and 1 to 5 parts of pigment.
[0009] Furthermore, the compatibilizer is a copolymer of maleic anhydride grafted ethylene and octene.
[0010] Furthermore, the antioxidant is one of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine.
[0011] Furthermore, the lubricant is one of calcium stearate, polyethylene wax or magnesium carbonate.
[0012] Furthermore, the pigment is carbon black.
[0013] The preparation method of the modified nylon comprises the following steps:
[0014] X1. Add methylene succinic acid to anhydrous ethanol to obtain solution A; add tetramethylene diamine to anhydrous ethanol to obtain solution B; add solution B to solution A, heat to 60-80°C, stir for 1-2 hours, cool to room temperature, filter, dry the residue, heat to 140-150°C in an inert atmosphere to melt, then heat to 150-160°C, keep for 2-3 hours, evacuate, melt polycondense for 4-6 hours, add tetramethylene diamine to stop the reaction, and obtain amino-terminated nylon;
[0015] X2, (bibenzyl-4,4'-diyl) diisocyanate and polytetrahydrofuran were mixed and heated for prepolymerization for 1 to 2 hours under an inert atmosphere, and then trimethylolpropane was added and the polymerization was continued for 1 to 2 hours. After the reaction was completed, it was directly used for the next step;
[0016] X3. Mix the amino-terminated nylon and the product of the previous step in a molar ratio of 1:1, heat and stir for 1 to 2 hours to polymerize to obtain the modified nylon.
[0017] Furthermore, the heating temperature in step X2 is 70-80°C.
[0018] Furthermore, the heating temperature in step X3 is 180-200°C.
[0019] Preferably, the preparation method of the modified nylon comprises the following steps:
[0020] X1. Add 10-15 parts by weight of methylene succinic acid to 50-100 parts by weight of anhydrous ethanol to obtain solution A; add 5-15 parts by weight of tetramethylene diamine to 30-50 parts by weight of anhydrous ethanol to obtain solution B; add solution B to solution A, heat to 60-80°C, stir for 1-2 hours, cool to room temperature, filter, dry the residue, heat to 140-150°C in an inert atmosphere to melt, then heat to 150-160°C, keep for 2-3 hours, evacuate, melt polycondense for 4-6 hours, add 2% of the residue weight of tetramethylene diamine to stop the reaction, and obtain amino-terminated nylon;
[0021] X2, 30-60 parts by weight of (bibenzyl-4,4'-diyl) diisocyanate and 100-250 parts by weight of polytetrahydrofuran are mixed and heated to 70-80°C under an inert atmosphere for prepolymerization for 1-2 hours, and then 20-40 parts by weight of trimethylolpropane are added and the polymerization is continued for 1-2 hours. After the reaction is completed, it is directly used in the next step;
[0022] X3. Mix the amino-terminated nylon and the product of the previous step in a molar ratio of 1:1, heat to 180-200°C and stir for 1-2 hours to polymerize to obtain the modified nylon.
[0023] A method for preparing a paint-free memory nano-nylon resin comprises the following steps:
[0024] S1. After mixing the raw materials according to the proportion, stirring and mixing at 80-100°C and a certain speed, mixing and extruding are performed;
[0025] S2. The extrudate is water-cooled and pelletized to obtain the product.
[0026] Furthermore, the rotation speed is 1000-1500 rpm.
[0027] Furthermore, the mixing temperature is 150-200°C.
[0028] Beneficial effects of the present invention:
[0029] 1. Compared with the prior art, the present invention uses amino-terminated nylon as a hard segment to provide rigidity inside the structure, polytetrahydrofuran is polymerized to obtain a soft segment, and the hard and soft segments are polymerized to obtain modified nylon. The soft and hard segments form a microphase-separated structure in the system. The construction of the microphase-separated structure plays a decisive role in shape memory. Therefore, the prepared modified nylon has strong rigidity and good flexibility.
[0030] 2. The nylon resin prepared by the present invention has good toughness and resilience, can be bent and twisted and restore its original shape, has a smooth surface, and does not require painting after molding. DETAILED DESCRIPTION
[0031] (Bibenzyl-4,4'-diyl) diisocyanate, CAS No.: 1034-24-8.
[0032] Polytetrahydrofuran, Mw=2000, model: DYT-005, Deyitai.
[0033] Styrene-butadiene-acrylonitrile copolymer, brand: TR-530F, Shanghai Yisufa New Materials.
[0034] Maleic anhydride grafted ethylene and octene copolymer, model: Dow 8137, Dongguan Yingxiang plastic raw materials.
[0035] Comparative Example 1
[0036] A method for preparing a paint-free memory nano-nylon resin comprises the following steps:
[0037] S1. 500 g of modified nylon, 150 g of styrene-butadiene-acrylonitrile copolymer, 80 g of maleic anhydride grafted ethylene and octene copolymer, 5 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 50 g of calcium stearate, and 20 g of carbon black were mixed, stirred and mixed at 80° C. and 1200 rpm, and then sampled and mixed at 160° C. and extruded;
[0038] S2. The extrudate is water-cooled and pelletized to obtain the product.
[0039] The preparation method of the modified nylon comprises the following steps:
[0040] X1. Add 130 g of methylene succinic acid to 650 mL of anhydrous ethanol to obtain solution A; add 90 g of tetramethylene diamine to 400 mL of anhydrous ethanol to obtain solution B; add solution B to solution A, heat to 70°C and stir for 1 hour, then cool to room temperature, filter, dry the residue, heat to 150°C in an inert atmosphere to melt, then heat to 160°C, keep for 3 hours, evacuate, melt polycondense for 6 hours, add 2% of the residue weight of tetramethylene diamine to stop the reaction, and obtain amino-terminated nylon;
[0041] X2, 500 g of (bibenzyl-4,4'-diyl) diisocyanate and 1900 g of polytetrahydrofuran were mixed and heated to 75°C for polymerization for 2 h under an inert atmosphere. After the reaction was completed, it was directly used in the next step;
[0042] X3. Mix the amino-terminated nylon and the product of the previous step in a molar ratio of 1:1, heat to 190°C and stir for 2 hours to polymerize to obtain the modified nylon.
[0043] Comparative Example 2
[0044] A method for preparing a paint-free memory nano-nylon resin comprises the following steps:
[0045] S1. 500 g of modified nylon, 150 g of styrene-butadiene-acrylonitrile copolymer, 80 g of maleic anhydride grafted ethylene and octene copolymer, 5 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 50 g of calcium stearate, and 20 g of carbon black were mixed, stirred and mixed at 80° C. and 1200 rpm, and then sampled and mixed at 160° C. and extruded;
[0046] S2. The extrudate is water-cooled and pelletized to obtain the product.
[0047] The preparation method of the modified nylon comprises the following steps:
[0048] Mix 1000g of caprolactam, 80g of caprolactone and 20g of sodium hydroxide, heat to 120°C, pump to negative pressure to remove water for 20min, stir for 1h, add 15g of (bibenzyl-4,4'-diyl) diisocyanate, and polymerize at 180°C for 1h.
[0049] Example 1
[0050] A method for preparing a paint-free memory nano-nylon resin comprises the following steps:
[0051] S1. 500 g of modified nylon, 150 g of styrene-butadiene-acrylonitrile copolymer, 80 g of maleic anhydride grafted ethylene and octene copolymer, 5 g of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 50 g of calcium stearate, and 20 g of carbon black were mixed, stirred and mixed at 80° C. and 1200 rpm, and then sampled and mixed at 160° C. and extruded;
[0052] S2. The extrudate is water-cooled and pelletized to obtain the product.
[0053] The preparation method of the modified nylon comprises the following steps:
[0054] X1. Add 130 g of methylene succinic acid to 650 mL of anhydrous ethanol to obtain solution A; add 90 g of tetramethylene diamine to 400 mL of anhydrous ethanol to obtain solution B; add solution B to solution A, heat to 70°C and stir for 1 hour, then cool to room temperature, filter, dry the residue, heat to 150°C in an inert atmosphere to melt, then heat to 160°C, keep for 3 hours, evacuate, melt polycondense for 6 hours, add 2% of the residue weight of tetramethylene diamine to stop the reaction, and obtain amino-terminated nylon;
[0055] X2, 500 g of (bibenzyl-4,4'-diyl) diisocyanate and 1900 g of polytetrahydrofuran were mixed and heated to 75°C for prepolymerization for 2 h under an inert atmosphere, and then 30 g of trimethylolpropane was added and the polymerization was continued for 2 h. After the reaction was completed, it was directly used in the next step;
[0056] X3. Mix the amino-terminated nylon and the product of the previous step in a molar ratio of 1:1, heat to 190°C and stir for 2 hours to polymerize to obtain the modified nylon.
[0057] Example 2
[0058] Compared with Example 1, the only difference is that the amount of styrene-butadiene-acrylonitrile copolymer is 120 g.
[0059] Example 3
[0060] Compared with Example 1, the only difference is that the amount of styrene-butadiene-acrylonitrile copolymer is 170 g.
[0061] Example 4
[0062] Compared with Example 1, the only difference is that the amount of carbon black is 10 g.
[0063] Example 5
[0064] Compared with Example 1, the only difference is that the amount of carbon black is 30 g.
[0065] Test Example 1
[0066] The mechanical properties of the nylon resin in the control example and the embodiment were tested with reference to the test method in GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", including tensile strength and elongation at break, with a tensile rate of 50 mm / min. The gloss of the nylon resin material was measured with reference to ISO2813-2014 "Paints and varnishes - Determination of gloss values at 20°, 60° and 85°".
[0067] Table 1 Mechanical properties and gloss test of nylon resin
[0068] Experimental protocol Tensile strength / MPa Elongation at break / % Gloss (60°) Comparative Example 1 130.1 200.4 88 Comparative Example 2 121.2 168.7 87 Example 1 138.6 350.3 89 Example 2 136.5 340.1 80 Example 3 137.3 341.6 90 Example 4 137.1 345.2 82 Example 5 133.2 325.4 90
[0069] As can be seen from Table 1, compared with the conventional shape memory nylon material in Control Example 2, the nylon resin prepared in the embodiment has significantly better tensile strength and resilience. This may be because the amino-terminated nylon in the embodiment provides rigidity as a hard segment inside the structure, and the soft segment is obtained after the polymerization of polytetrahydrofuran, and the modified nylon is obtained after the polymerization of the hard and soft segments. The soft and hard segments form a microphase separation structure in the system. The construction of the microphase separation structure plays a decisive role in shape memory, so the prepared modified nylon has strong rigidity and good flexibility. In Control Example 1, when polytetrahydrofuran is used as the matrix to obtain the soft segment, trimethylolpropane is not added, so the final soft segment structure is smaller and has fewer crosslinking points, which leads to a lower crosslinking degree of the modified nylon, affecting the mechanical properties of the material. When the soft and hard segments of Example 1 are polymerized, there are multiple crosslinking sites, so a more compact structure can be formed. Compared with Example 1, the amount of styrene-butadiene-acrylonitrile copolymer in Examples 2 to 3 is different, so the glossiness of the material is different, but Example 3 is not much different from Example 2. Compared with Example 1, Examples 4 to 5 have different amounts of carbon black, which will result in different black brightness of the material and affect the glossiness. However, the dispersibility of carbon black is poor. Too much carbon black will affect the mechanical properties of the material. Therefore, the material performance in Example 1 is relatively optimal.
[0070] Test Example 2
[0071] The shape memory test of the nylon resin prepared in the control example and the embodiment is carried out. The test method is to keep a sample with a length of L0 at a constant temperature of 80°C for 10 minutes, stretch the sample at a stretching speed of 10 mm / min to 200% deformation, keep it for 10 minutes, reduce the temperature to 30°C, crystallize the sample for 10 minutes, record the length of the sample at this time as L1, remove the stress, and test the length of the sample L2 after 10 minutes; heat it up to 230°C again, keep it for 10 minutes, cool it to 30°C again, keep it for 30 minutes, and record the length of the sample L3; shape fixation rate: R f =(L2-L0) / (L1-L0)×100% Shape recovery rate: R r =(L2-L3) / (L2-L0)×100%.
[0072] Table 2 Shape memory test of nylon resin
[0073]
[0074]
[0075] The nylon resin in the present invention is composed of hard segments and soft segments, and there is a two-phase separated aggregate structure in the system. The melting point or glass transition temperature of the soft segment is low, while the melting point or glass transition temperature of the hard segment is usually high, so it has shape memory properties. The amino-terminated nylon on the main chain is used as the stationary phase, and the polymer obtained from polytetrahydrofuran is a reversible phase. Through processing deformation, the material is given shape memory properties, which can cause material changes when experiencing stimuli such as deformation or temperature changes, but because the material has good resilience, it can quickly return to its original shape. From the shape memory test, it can be seen that the nylon resins prepared in the examples all have good resilience, and the shape test data of Examples 1 to 5 are not much different. This may be because the shape memory performance itself is most related to the modified nylon, and the amount of modified nylon in the examples is the same, but the stretchability will still affect the morphology after deformation to a certain extent, so the shape memory performance between the examples is also different. Compared with the comparative example 1, in Example 1, since trimethylolpropane was not added when the soft segment was obtained by using polytetrahydrofuran as the matrix, the soft segment structure finally obtained was smaller and had fewer crosslinking points, resulting in a lower crosslinking degree of the modified nylon, while the soft segment orientation obtained in Example 1 was larger, so the rebound was better. Compared with the comparative example 2, in Example 1, the amino-terminated nylon provided rigidity inside the structure as a hard segment, the soft segment was obtained after the polymerization of polytetrahydrofuran, and the modified nylon was obtained after the polymerization of the hard and soft segments, and the soft and hard segments formed a microphase separation structure in the system, and the construction of the microphase separation structure played a decisive role in shape memory, so the prepared modified nylon had better flexibility.
[0076] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A paint-free memory nano nylon resin, characterized in that: The invention comprises the following raw materials in parts by weight: 40-70 parts of modified nylon, 10-20 parts of styrene-butadiene-acrylonitrile copolymer, 5-10 parts of compatibilizer, 0.5-5 parts of antioxidant, 2-10 parts of lubricant and 1-5 parts of pigment; The preparation method of the modified nylon comprises the following steps: X1. Add 10 to 15 parts by weight of methylene succinic acid to 50 to 100 parts by weight of anhydrous ethanol to obtain solution A; add 5 to 15 parts by weight of tetramethylene diamine to 30 to 50 parts by weight of anhydrous ethanol to obtain solution B; Add solution B to solution A, heat to 60-80°C, stir for 1-2 hours, cool to room temperature, filter, dry the residue, heat to 140-150°C in an inert atmosphere to melt, then heat to 150-160°C, keep for 2-3 hours, evacuate, melt polycondense for 4-6 hours, add 2% of the residue weight of tetramethylene diamine to stop the reaction, and obtain amino-terminated nylon; X2, 30-60 parts by weight of (bibenzyl-4,4'-diyl) diisocyanate and 100-250 parts by weight of polytetrahydrofuran were mixed and heated to 70-80°C under an inert atmosphere for prepolymerization for 1-2 hours, and then 20-40 parts by weight of trimethylolpropane were added and the polymerization was continued for 1-2 hours. After the reaction was completed, it was directly used in the next step; X3. Mix the amino-terminated nylon and the product of the previous step in a molar ratio of 1:1, heat to 180-200°C and stir for 1-2 hours to polymerize to obtain the modified nylon.
2. The paint-free memory nano nylon resin according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted ethylene and octene copolymer.
3. The paint-free memory nano nylon resin according to claim 1, characterized in that: The antioxidant is one of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine.
4. The paint-free memory nano nylon resin according to claim 1, characterized in that: The lubricant is one of calcium stearate, polyethylene wax or magnesium carbonate.
5. The paint-free memory nano nylon resin according to claim 1, characterized in that: The pigment is carbon black.
6. The method for preparing the paint-free memory nano nylon resin according to any one of claims 1 to 5, characterized in that: The steps include: S1. Mix the raw materials according to the proportion, stir and mix at 80-100℃ and a certain speed, then mix and extrude; S2. The extrudate is water-cooled and pelletized to obtain the product.
7. The method for preparing the paint-free memory nano-nylon resin according to claim 6, characterized in that: The rotation speed is 1000-1500 rpm, and the mixing temperature is 150-200°C.
Citation Information
Patent Citations
Memory nylon rubber and plastic material and preparation method thereof
CN103992638A
A nylon 6 composition with excellent shape memory properties and its preparation method
CN114479436B
Spray-free polyamide compound with metallic luster and preparation method thereof
CN107216649A
High flow non-spraying metallic silver polyamide composition and preparation method thereof
CN108559258A